Young elite Alpine and Mogul skiers have a higher prevalence of cam morphology than non-athletes - Aminoff, Anna Swärd; Agnvall, Cecilia; Todd, Carl; Jónasson, Páll; Thoreson, Olof; Sansone, Mikael; Swärd, Leif; Karlsson, Jon; Baranto, Adad (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2020)
Purpose To investigate the prevalence of cam morphology in (1) a group of young elite Mogul and Alpine skiers compared with non-athletes and (2) between the sexes. Method The hip joints of 87 subjects [ n = 61 young elite skiers (29 females and 32 males) and n = 26 non-athletes (17 females and 9 males)] were examined using MRI, for measurements of the presence of cam morphology ( α -angle ≥ 55). Results The skiers had a significantly higher prevalence of cam morphology compared with the non-athletes (49% vs 19%, p = 0.009). A significant difference ( p < 0.001) was also found between females and males, where 22% of the females and 61% of the males had cam morphology. Among the skiers, there was also a significant difference ( p < 0.001) between the sexes, where 28% of the females and 68% of the males had cam morphology. This difference between the sexes was not found in the non-athletic group. No significant differences were found between Mogul and Alpine skiers. Conclusion Young male elite skiers have a higher prevalence of cam morphology of the hips compared with non-athletes. Level of evidence II.